2014
DOI: 10.1073/pnas.1404807111
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by the BLM helicase correlates with the presence of G-quadruplex DNA motifs

Abstract: Significance Bloom syndrome is a rare human genetic disease characterized by proportional dwarfism, immunodeficiency, and an elevated risk of many different cancer types. We used RNA expression profiling to identify networks of mRNAs and microRNAs that are differentially expressed in cells from Bloom syndrome patients and associated with cell proliferation, survival, and molecular pathways promoting cancer. Altered mRNA expression was in some cases strongly correlated with the presence of G4 motifs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 51 publications
5
94
1
1
Order By: Relevance
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussionmentioning
confidence: 56%
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussionmentioning
confidence: 56%
“…These facts suggest G-quadruplex structures have implications in physiological processes. Indeed, experimental investigations have demonstrated the physiological function of G-quadruplexes in many aspects (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…A recent study is done on fibroblast line cells that explain the role of redox alterations in cells, in BS phenotype. This shows the increased levels of SOD activity and overproduction of ROS in BS cells [24].…”
Section: Role Of Antioxidantsmentioning
confidence: 82%